Focused on earnings management of manufacturing sector in the V4 region - Durana Pavol (SHS Web of Conferences, 2021)
Research background: Earnings management is global phenomenon of legal manipulation. The number of the examinations related to earnings management in the V4 region has been increased. These international studies identified the manipulation between countries and for different periods of years, but the assessment of individual sectors has been still missing. The article focused on sector manufacturing and its earnings management to gain global view of this issue for this region. Purpose of the article: The basic purpose and the selected aim of provided study was to detect the status of the activities of earnings management between the enterprises in the V4 region in set sector of the national economies. Methods: The realized financial study used 1,612 Slovak, Czech, Hungarian, and Polish enterprises from sector “C” manufacturing. Discretionary accruals were computed by the Modified Jones for the year 2019. One-way Anova was run for this investigation to test delivered hypotheses of the paper. Additionally, Scheffe’s procedure was computed to identify significant differences in manipulation of the earnings between individual countries. Findings & Value added: The article detected that there was difference between earnings management in the V4 region based on selected sample of enterprises from the sector manufacturing. Post hoc comparisons showed that significant discrepancy in earnings manipulation was between Slovak and Hungarian enterprises in 2019 on one hand. On the other hand, similar approach was between other emerging countries.